(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The article defines theoretical aspects of social and ethical marketing. The interpretation of the concept of «socio-ethical marketing» by foreign and domestic scholars is analyzed. The main advantages of the concept of socio-ethical marketing, which are realized through its modern functions: analytical, production, pricing, sales, communication, strategic, managerial, informative, social, reproductive, are considered. Three ideas that form the basis of social and ethical marketing are described. Public, social, economic goals and principles of socio-ethical marketing are defined: objectivity, adequacy, orderliness, sustainability, awareness, balance, social responsibility, moral responsibility, publicity and transparency. The directions of application of social and ethical marketing are characterized. The spheres of economic activity in which the use of social and ethical marketing is particularly important are presented. The advantages, positive and negative consequences of the application of socio-ethical marketing in the public administration system are considered.